2014
DOI: 10.1007/s40596-014-0080-4
|View full text |Cite
|
Sign up to set email alerts
|

Training Psychiatrists for Rural Practice: A 20-Year Follow-up

Abstract: Purposeful and well-coordinated educational opportunities situated in rural community health clinics can address some of the barriers for recruiting and retaining practicing psychiatrists in rural areas. Practical skill building at the individual, agency, and system level is integral in training psychiatrists for work in these communities. In particular, the use of telepsychiatry emerged as an important practical application for the provision of rural mental health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
9
1
Order By: Relevance
“…In a 20-year follow-up study of the University of New Mexico Rural Psychiatry Residency Program, Bonham et al [24] found that 37% of graduates practice in rural communities in comparison to 10% of graduates from the traditional residency track. The rural track involved community site visits in postgraduate years (PGY) 2 and 3 and longitudinal community work (2 days per week, throughout the year) during PGY-4; encouragement to participate in community activities such as support groups and networking with tribal governments; and attendance at the biannual meeting of the Rural and Community Psychiatry Network of New Mexico.…”
Section: The Role Of Psychiatric Educatorsmentioning
confidence: 99%
“…In a 20-year follow-up study of the University of New Mexico Rural Psychiatry Residency Program, Bonham et al [24] found that 37% of graduates practice in rural communities in comparison to 10% of graduates from the traditional residency track. The rural track involved community site visits in postgraduate years (PGY) 2 and 3 and longitudinal community work (2 days per week, throughout the year) during PGY-4; encouragement to participate in community activities such as support groups and networking with tribal governments; and attendance at the biannual meeting of the Rural and Community Psychiatry Network of New Mexico.…”
Section: The Role Of Psychiatric Educatorsmentioning
confidence: 99%
“…Traditional clinical training partnerships increase the workforce in underserved areas by recruiting students from rural areas, utilizing distance learning, or sending students to rural training sites in a residency or internship format (Bonham et al, 2014; Soltis-Jarrett, 2011). However, universities and partner organizations seeking to train new providers are limited by an inadequate number of clinical educators and training sites.…”
Section: Introductionmentioning
confidence: 99%
“…15 A small amount of graduate medical education (GME), however, occurs in rural settings in high-need specialties such as family medicine, 16 internal medicine, 9 general surgery, 17,18 and psychiatry. 19 Osteopathic residency programs contributed more growth to rural GME over 10 years (2005-2015) than allopathic programs, 20 but the transition by 2020 to a single allopathic and osteopathic GME accreditation system operated by the Accreditation Council for Graduate Medical Education (ACGME) has uncertain implications for small and rurally focused residency programs, particularly osteopathic programs. Osteopathic programs outside of generalist specialties could be vulnerable because these programs tend to have fewer residents than allopathic programs, and rural programs are more often smaller.…”
Section: Introductionmentioning
confidence: 99%